Analysis of the Performance of the Bolabaket Bhayangkara Bea Cukai Jaya (BBJ) Team in Participating in the Surabaya Champion League (SCL) 2022 - Gigih Siantoro; Bhekti Lestari; Oki Indro Priambodo; Bayu Agung Pramono (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
Performance analysis through match statistics has developed and is inseparable from individual or team sports to observe and evaluate individual or team playing performances. This study aims to analyze four indicators of playing performance in FIBA Live stats match statistics, namely field goal percentage (FG%), free throw percentage (FT%), rebounds (REB), and turnovers (TOV) from the Bhayangkara Bea Cukai Jaya (BBJ) Basketball team in participating in the Surabaya Champion League 2022. This research is quantitative descriptive research with descriptive statistical analysis. The analysis results show that the average field goal percentage (FG%) is 29.82%, with eight players above the average and seven below the norm to be concluded in the